Conflict-Specific Aging Effects Mainly Manifest in Early Information Processing Stages—An ERP Study with Different Conflict Types - Korsch, Margarethe; Frühholz, Sascha; Herrmann, Manfred (Frontiers in Aging Neuroscience, 2016)
Aging is usually accompanied by alterations of cognitive control functions such as conflict processing. Recent research suggests that aging effects on cognitive control seem to vary with degree and source of conflict, and conflict specific aging effects on performance measures as well as neural activation patterns have been shown. However, there is sparse information whether and how aging affects different stages of conflict processing as indicated by event related potentials (ERP) such as the P2, N2 and P3 components. In the present study 19 young and 23 elderly adults performed a combined Flanker conflict and stimulus-response-conflict (SRC) task. Analysis of the median reaction times revealed an increased SRC related conflict effect in elderly. ERP analysis furthermore demonstrated an age-related increase of the P2 amplitude in response to the SRC task. In addition, elderly adults exhibited an increased P3 amplitude modulation induced by incongruent SRC and Flanker conflict trials.